Taurus - Moorey, Teresa (Reach your potential., 1998)
This guide aims to help Taurean readers reach their full potential by examining their star sign, making the most of their assets, benefitting from their weak points, excelling at work and succeeding in relationships. It also describes how compatible Taureans are with every other birth sign.